(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: The dandruff is one of the common skin conditions among adolescents. World 50% of the general population and is mostly seen in males than females among adolescents Methods: A quantitative research approach was adopted to assess the knowledge on prevention and management of dandruff among adolescents. Non- probability convenience sampling technique was used to select the sample. Result: The findings of the study that 15% of the subjects were having good knowledge, 82% were having average knowledge and 3% were having poor knowledge. There is a significant association found knowledge sore and the type of family. Conclusion: The study revealed that there is need of awareness program for regarding prevention and management of dandruff for adolescents.